2020
DOI: 10.3847/1538-4357/ab9f9c
|View full text |Cite
|
Sign up to set email alerts
|

Distances and Statistics of Local Molecular Clouds in the First Galactic Quadrant

Abstract: We present an analysis of local molecular clouds ( km s−1, i.e., <1.5 kpc) in the first Galactic quadrant ( and ), a pilot region of the Milky Way Imaging Scroll Painting (MWISP) CO survey. Using the Spectral Clustering for Interstellar Molecular Emission Segmentation algorithm to divide large molecular clouds into… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 61 publications
2
66
0
Order By: Relevance
“…In the Milky Way, GMCs have long been known as good tracers of spiral arms (e.g., Myers et al, 1986;Grabelsky et al, 1988;Hou and Han, 2014). From the wealthy dataset of Galactic CO surveys (see Heyer and Dame, 2015, for a review), a large number of isolated molecular clouds have been identified by different methods (e.g., García et al, 2014;Rice et al, 2016;Miville-Deschênes et al, 2017;Yan et al, 2020;Duarte-Cabral et al, 2021). For the majority of them, only kinematic distances are known, which depend on the adopted Galaxy rotation curve, the solution of the kinematic distance ambiguity, and deviation from the hypothetic circular rotation.…”
Section: Giant Molecular Cloudsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Milky Way, GMCs have long been known as good tracers of spiral arms (e.g., Myers et al, 1986;Grabelsky et al, 1988;Hou and Han, 2014). From the wealthy dataset of Galactic CO surveys (see Heyer and Dame, 2015, for a review), a large number of isolated molecular clouds have been identified by different methods (e.g., García et al, 2014;Rice et al, 2016;Miville-Deschênes et al, 2017;Yan et al, 2020;Duarte-Cabral et al, 2021). For the majority of them, only kinematic distances are known, which depend on the adopted Galaxy rotation curve, the solution of the kinematic distance ambiguity, and deviation from the hypothetic circular rotation.…”
Section: Giant Molecular Cloudsmentioning
confidence: 99%
“…The distance uncertainties of 11 clouds were ≲ 10%. With the same method, Yan et al (2020) determined the distances for 28 local molecular clouds (d < 1.5 kpc, here d is the distance to the Sun) in the first Galactic quadrant. The distances for 76 molecular clouds were measured in the second Galactic quadrant by Yan et al (2021).…”
Section: Giant Molecular Cloudsmentioning
confidence: 99%
“…Before measuring distances, we drew molecular cloud samples using the method developed by Yan et al (2020), which is based on the DBSCAN clustering algorithm 4 . DBSCAN identifies connected structures in position-position-velocity (PPV) space, paying no attention to the internal structure, the morphology, or the scale of molecular clouds.…”
Section: Molecular Cloud Identificationmentioning
confidence: 99%
“…In PPV space, corresponds to three connectivity types ( = 1, √ 2, and √ 3), and, for high values of , MinPts also needs to be high to avoid including too many noise samples. Yan et al (2020) found that, for appropriate lower MinPts values, the three connectivity types yield similar cloud samples, so we used connectivity 1 ( = 1) and MinPts 4. The minimum cutoff on the PPV data cubes is 2σ (∼1 K).…”
Section: Molecular Cloud Identificationmentioning
confidence: 99%
See 1 more Smart Citation